Taxonomic revision of the Dichotomius speciosus (Waterhouse, 1891) species group (Coleoptera: Scarabaeidae: Scarabaeinae) - Maldaner, Maria E.; Nunes, Rafael V.; Vaz-De-Mello, Fernando Z. (Zootaxa, 2015)
The Dichotomius speciosus species group, endemic to the highlands of the Brazilian Atlantic Forest and included in the subgenus Luederwaldtinia is taxonomically revised. Dichotomius alvarengai new species and D. malyi new species are described. Dichotomius bucki is here considered to be a new synonym of D. opalescens, for which a lectotype is designated. The group, as well as its species, is diagnosed. A taxonomic key, illustrations and discussions on systematics and conservation of the group are provided.